2009
DOI: 10.1158/1078-0432.ccr-08-2439
|View full text |Cite|
|
Sign up to set email alerts
|

Suppression of Tumor GrowthIn vivoby the Mitocan α-tocopheryl Succinate Requires Respiratory Complex II

Abstract: Purpose: Vitamin E analogues are potent novel anticancer drugs. The purpose of this study was to elucidate the cellular target by which these agents, represented by a-tocopoheryl succinate (a-TOS), suppress tumors in vivo, with the focus on the mitochondrial complex II (CII). Experimental Design: Chinese hamster lung fibroblasts with functional, dysfunctional, and reconstituted CII were transformed using H-Ras. The cells were then used to form xenografts in immunocompromized mice, and response of the cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 55 publications
5
107
0
Order By: Relevance
“…In fact, tumors derived from complex II-mutated cells were more resistant to a-TOS in vivo and complex I-defective cells displayed normal sensitivity to a-TOS in vitro, suggesting that a-TOS specifically targets complex II. 30 However, reverse electron transfer from succinate and complex II to complex I generates ROS. 24,31 In a model of reverse electron transfer induced by a-TOS, the primary site of ROS production would be complex I, so the action of the drug would be impaired by a complex II target deletion.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, tumors derived from complex II-mutated cells were more resistant to a-TOS in vivo and complex I-defective cells displayed normal sensitivity to a-TOS in vitro, suggesting that a-TOS specifically targets complex II. 30 However, reverse electron transfer from succinate and complex II to complex I generates ROS. 24,31 In a model of reverse electron transfer induced by a-TOS, the primary site of ROS production would be complex I, so the action of the drug would be impaired by a complex II target deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Different inhibitors of complex I (for example, tamoxifen; Moreira et al, 2006), complex II (for example, fenretinide; Cuperus et al, 2010) or complex III (for example, adaphostin; Le et al, 2007) markedly induce ROS and apoptosis in tumour cells. One of the most promising drugs in this field is the vitamin E derivative a-tocopheryl succinate (Dong et al, 2007(Dong et al, , 2008(Dong et al, , 2009) and its mitochondrial targeted analogue mitoVES (Dong et al, 2011a, b) developed by the Neuzil group. These compounds were shown to specifically target the Q P site of complex II for ROS generation by enzymatic uncoupling (see above) and elicit apoptosis induction in tumours in vitro and in vivo.…”
Section: Rc-based Strategies In Cancer Therapy?mentioning
confidence: 99%
“…a-TOS, a compound epitomising the 'mitocan' group of anticancer agents (Neuzil et al, 2007a), was found to induce cell death by generation of superoxide anion radicals by targeting complex II of the mitochondria respiratory chain (Dong et al, 2008(Dong et al, , 2009. ROS, in turn, promote apoptosis by catalysing the formation of disulfite bridges between monomeric Bax, resulting in the formation of mitochondrial outer membrane channel.…”
Section: Discussionmentioning
confidence: 99%
“…One of the emerging targets for anti-cancer drugs is mitochondria that is central to induction of programmed cell death (Gogvadze et al, 2008;Trachootham et al, 2009). Our previous work has identified mitochondria as transmitters of apoptosis induced by the redox-silent analogue of vitamin E (VE) a-tocopheryl succinate (a-TOS) (Neuzil et al, , 2007a) that is selective for cancer cells (Neuzil et al, 2001a, b) and suppresses tumours in a variety of pre-clinical models (Neuzil et al, 2001b;Stapelberg et al, 2005;Wang et al, 2007;Dong et al, 2008Dong et al, , 2009). This suggests that the VE analogue is a promising anti-cancer drug that may suppress tumours by causing cell death of malignant cells as well as synergizing with other anti-cancer agents.…”
mentioning
confidence: 99%